Crystal-melt ± fluid equilibria versus late-stage fluid - rock interaction in granitoid rocks of the South Mountian Batholith, Nova Scotia: whole rock geochemistry and oxygen isotope evidence - Kontak, Daniel J.; Strong, David F.; Kerrich, Robert (Atlantic Geoscience, 1988)
The chemical and oxygen iaotopic evolution of the 370 Ma. peraluminous South Mountain Batholith of Nova Scotia baa been examined. The chemistry of early- to late-stage magmatic suites is uniform with respect to most major and trace elements, including the rare earth elements (REE). The continuity of the chemistry reflects the dominant role of melt-crystal equilibria during progressive fractionation of the melt through the sequence granodiorite-monzogranite-leucogranlte (group I). However, leucogranites (group II) associated with pegmatite occurrences In the Hew Ross area have chemical signatures, especially their RHB patterns (extreme LREB depletions and concave HREB profiles peaking at Gd-Dy), which indicate that fluid-phase equilibria played an important role In the evolution of these rocks. Whole-rock oxygen-isotope compositions are uniform at 10.6 ± 0.5 %o (N-14) regardless of proximity to contacts. degree of fractionation or presence of late-stage deuterlc alteration. The observed variation (ca. 1.8 %o) la attributed to primary heterogeneity in the source region, and not crystal fractionation processes. Mijwral separates from pegmatites indicate deviations from magmatic equilibrium based on quartz-feldspar fractionation. This is interpreted to reflect re-equilibration of feldspar with low temperature fluids of magmatic derivation calculated (δ18O of the fluid is 7-10%o). In contrast, one of the grelsens examined records interaction with 0 enriched fluids (calculated (δ18O composition of 11.5-14 %o for T-300-400oC), which were probably derived from the enveloping meta-sediaentary country rock (i.e.. Meguma Group). A low 18O value (3.6 %o) for one whole-rock sample Indicates that meteoric water also played a role, albeit minor. In the evolution of the batholith. RÉSUMÉ On a examiné l’évolution de la chimie et des isotopes de l’oxygène dans le Batholite péraluraineux de South Mountain (date à 370 Ha) en Nouvelle-Écosse. Le diiraisme des suites magmatiques, taut tardives que précoces, est unlforme en ce qui à trait à la plupart des éléments majeurs et en traces, y comprises lea terrea rares (T.R.). Cette continuité du chimisrme met en lumière le rôle prépondérant joué par les équilibres bain-cristal durant le fractlonnement progressif de ce bain via la aerie granodiorite-raonzogranite-leucogranite (groupe I). En revanche, les leucogranites du groupe II, associés aux venues pegraatitiqueaédans la région de New Ross, out des signatures chimiques (plus particulièrement des spectres de terres rares extreroement appauvris en T.R. légères et montrant des profils concaves pour lée T.R. lourdes avec dea anomalies positives à Gd-Dy) qui mettent en évidence le role majeur Joue par les équilibres fluide-phase dans l’évolution de ces roches. Les compositions isotopiques de l’oxygène sur roche totale sont uniformes à 10,6 ± 0,5 %o (N-14) peu importent la proximité des contacts, le degré de fractlonnement ou la présence d’altérations deutériques tardives. On attribue la variation observée (environ 1,8 %o) à une hétérogènéité primèire de la source et non pas aux processus de fractlonnement des cristaux. Les minéraux separes des pegmatites montrent des deviations par rapport à l’équillbre raagmatlque base sur le fractionnement des quartz et feldagaths, ce qui semble trahir un ré-équilibrage du feldspath avec des fluides de température faible issus du magma (δ18O caleule du fluide est 7-10 %o), Par contre. un des greisens examinés met en lumière une interaction avec des fluides enrichis en (δ18O caleule 11,5-14 %o pour T-300-400oC) derives probablement de l’encaissant métaéedimentaire (i.e., le Groupe de Heguma). Une faible valeur du 18O (3,6 %o) en provenance d’un seul échantillon sur roche totale indique que lea eaux méteoriques ont auasi joue un rôle, quoique mineur, dans l’évolution du batholite. [Traduit par le journal]